The Prevention of Tooth Wear. (2nd November 2020) - Mehta, Shamir B; Banerji, Subir
Abstract : With adult dentitions being retained for longer, issues relating to the wear of teeth are increasingly becoming of relevance to the general dental practitioner. As with any treatment plan, prevention is a fundamental and an important stage in the management of tooth wear. This article outlines the contemporary preventive features that the general dental practitioner should be aware of when dealing with patients presenting with tooth wear or exhibiting a susceptibility to this. CPD/Clinical Relevance: An understanding of the factors relevant to the prevention of tooth wear will enable an effective preventive regimen to be prescribed. This will play an integral role in the management of tooth wear and its sequalae.